Students Perception of ICT for Specific Purpose in The Logistics Industry - Rahmaniah; Iwan Setiawan (Borneo Educational Journal (Borju), 2023)
In today's dynamic and competitive world, logistics knowledge has become more complicated and knowledge intensive. Regarding the topic of TESOL in the logistic sector, which is the use of English as a foreign language and a current economic necessity, the use of English as a foreign language is one of the economic sources for boosting the employability of workers through superior communication skills. This study tries to answer the question of how students in the logistics industry perceive the use of ICT in English language learning. This research chapter addresses the importance of logistics education from the perspective of undergraduates. Using a quantitative methodology and survey design, the current study examined the frequency of ICT usage for purposes. The majority of students said that the usage of ICT makes it easier and more interesting for them to study English, is a good way for instructors to distribute learning materials, improves their speaking and listening abilities, and expands their vocabularies. Students and instructors can communicate, share, and discuss course materials and assignments effectively through the use of ICT and the logistics theme